Muscarinic cholinoceptor activation modulates DNA synthesis and CD40 expression in fibroblast cells - Casanova, M. (2006)
1 The aim of the present work was to examine the role of muscarinic acetylcholine receptors (mAChR) on DNA synthesis and CD40 expression in human fibroblast cells. Neonatal human skin fibroblast cultures were stimulated with carbachol in presence or absence of specific antagonists and the following parameters were measured: identification of mAChR subtypes, DNA synthesis, inositol phosphates (InsP) production and CD40 expression. 2 Human fibroblasts express mAChR with Kd 0.47 ± 0.11 nm and Bmax 236 ± 22 fmol mg protein-1. Carbachol stimulates DNA synthesis, InsP and the expression of CD40. All these effects were inhibited by atropine, mustard hydrochloride (4-DAMP) and pirenzepine but not by AF-DX 116 and tropicamide, indicating that M3 and M1 mAChR are implicated in carbachol action. The relative Ki of the antagonists obtained by competition binding assay was in parallel to the relative potency for blocking both carbachol-stimulated InsP accumulation and DNA synthesis. 3 The intracellular pathway leading to carbachol-induced biological effects involved phospholipase C and calcium/calmodulin, as U-73122 and trifluoroperazine blocked carbachol effects, respectively. Calphostin C, a protein kinase C inhibitor, had no effect, indicating that this enzyme does not participate in the system. 4 These results may contribute to a better understanding of the modulatory role of the parasympathetic muscarinic system on normal human fibroblast function.